Constitutional legal basis of ownership of natural resources in post-conflict societies as a factor of stability. (Journal of actual problems of jurisprudence, 2016)
The paper deals with of ownership of natural resources in post-conflict societies. Ownership issues are one of the major sources of tension. The article analyzes the constitutional norms of different countries, establishing the right of ownership over natural resources. Moreover paper also considers the constitutional legal agreement between theconflicting parties as a source which deals with questions of nature use. From this perspective, it is important that a clear definition of property rights is one of the most important aspects of public consent.
Keywords: natural resources; ownership; federations; autonomies; use of nature